What if utilitarian products are regarded as high-status? The moderate role of iconic and popular as two dimensions of brand coolness - Aleem, A.; Loureiro, S. M. C.; Schivinski, B.; Aguiar, M. (Journal of Marketing Communications, 2024)
This study aims to explore the moderator role of popular and iconic coolness dimensions on the relationship between hedonic versus utilitarian beauty product brands and high-status perceptions, using internet memes as stimuli. An experimental study was conducted to analyse whether two dimensions of brand coolness (popular and iconic) moderate the relationship between type of internet meme (utilitarian versus hedonic) and high-status. After conducting a pre-test, two internet memes were created for each condition, utilitarian and hedonic. In total, 428 completely answers were collected from an online MTurk panel, and the hypotheses were tested using moderation analysis. The results indicate that (i) hedonic brands are perceived as being high-status in the presence of both moderators (iconic and popular); (ii) utilitarian brands can be associated with high-status perceptions, if moderated by the popular dimension. Findings demonstrate that the popularity of the brand plays an important role in consumers perceptions. This study contributes to the marketing literature by analysing the relationship between three core dimensions of brand coolness, namely, iconic, popular, and high-status, regarding brands associated with hedonics and utilitarian products.